A transcriptional profile of aging in the human kidney. - Graham E J Rodwell; Rebecca Sonu; Jacob M Zahn; James Lund; Julie Wilhelmy; Lingli Wang; Wenzhong Xiao; Michael Mindrinos; Emily Crane; Eran Segal; Bryan D Myers; James D Brooks; et al. (PLoS Biology)
In this study, we found 985 genes that change expression in the cortex and the medulla of the kidney with age. Some of the genes whose transcripts increase in abundance with age are known to be specifically expressed in immune cells, suggesting that immune surveillance or inflammation increases with age. The age-regulated genes show a similar aging profile in the cortex and the medulla, suggesting a common underlying mechanism for aging. Expression profiles of these age-regulated genes mark not only age, but also the relative health and physiology of the kidney in older individuals. Finally, the set of aging-regulated kidney genes suggests specific mechanisms and pathways that may play a role in kidney degeneration with age.